KOMERSIALISASI PENDIDIKAN AGAMA ISLAM DI KABUPATEN BONE (STUDI KASUS SD IT) - R, Riskawati (JURNAL AL-QAYYIMAH, 2022)
AbstractFinancing in the context of education is financing to fund the procurement of all elements and activities carried out, so that all the programs offered are carried out properly, especially quality education, because to produce quality output requires quality systems and processes as well, because to produce quality output requires quality systems and processes as well. Thus, education is an activity that requires financing, however, education funding does not mean it has to be expensive, because expensive education funding does not necessarily mean it is of high quality. Education, which was originally a process of humanization and social transformation, has now experienced a distortion, becoming a commercial field for obtaining and accumulating wealth privately. Funding for education does exist, but the size of the funding for education depends on the programs and activities carried out, because the results of education also depend on both. The high cost of education funding that is not commensurate with its quality, can be pointed out as an indicator of efforts solely to gain profit, and at a certain level is categorized as the commercialization of education. Thus, the high cost of education financing can be caused by two factors. First, it is expensive because of education funding, such as because of the procurement of facilities and infrastructure needed to carry out the educational process in order to produce quality education. Second, the high cost of education funding is due to commercialization. The commercialization of education can occur due to various factors, including the result of the ideology of liberalism capitalism, the mentality of human resources, the granting of partial or full financing autonomy to educational institutions so as to provide wide opportunities to attract education funding for the sole benefit of profit. However, the schools examined by the researchers provided evidence that the legitimacy of these schools provided the basis and evidence for the non-commercialization of Islamic religious education, this was really just a statement from outside the school community.Keywords: Commercialization; Islamic education;  IT elementary school.